ANATOMIC STUDIES ABOUT RABBIT SPERMATICS WAYS - CARMEN BERGHES; MONICA PARVU; D. CUCA (Scientific Papers Animal Science and Biotechnologies, 2023)
The paper aims to bring some completions of male genital anatomy in rabbits, in particular related to vascularisatia it. Data from literature are brief and last time the species is used as a laboratory experimental model with application in human surgery. To study were used 10 animals that were purchased from the private sector. Prior to making dissection vascular formations were injected with a contrast material prepared in the laboratory of anatomy of the faculty. Dissection was performed using the magnifying glass stereomicroscopica and appropriate instrumentation surgery high fineness. Were achieved after pictures and pieces of dissection were performed schemes. Formation to describe the terminology used in NAV ed. 2002 After dissection found that epididyme is intimately attached to the edge epididymis testicularis, channel epididymis presents a many flecsuosis branch of different sizes, thickness of the channel increases from epididimar cones related to deferential channel, number eferente cones is variable (between 6 and 8 cones), and tail origin epidydimis and deferential channel is dressed in adipose tissue forming the body fat of testicularis. Testicular arteries originate from the abdominal aorta, right testicular artery, the right of the fifth lumbar vertebrae left testicular artery and the right of the sixth lumbar vertebra: epididimara artery skull emerges from the testicular artery and the caudal artery of the internal iliac .